Fascia Fitness Application: Internal Transformation - Sundar, Tanesh; Ab.Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2023)
Fascia fitness website is specifically designed to help peoples that are suffering from chronic pain, injuries and to build up performance for the sports that is played by an individual. However, the website had a difficulty in registration due to inconsistency, it was not convenient and the website lacks security and data privacy. Therefore, a well composed fascia fitness application is required to address the mentioned problems, the new application should have the ability to manage the data including the customers privacy and solving the register and login error that occurs often in the fascia fitness website. This fascia fitness application will be more secure and more functional to the customers. The main purpose of this fascia fitness application is to design and build an effective application to improve every aspect that was lacking in the fascia fitness website and also to benefit the users by becoming injury free. The methodology that was used is Agile model as it has the potential finish the system efficiently as this project is considered as small project and the project should be delivered in a short period of time. The application is developed using Object Oriented Approach (OOP) which is Java programming language in Android Studio. This application will let the user to register and sign into the account. After that, user will be able to choose the desired program to start the exercise. Users also can choose video and tips for a better understanding about fascia. Through this application, user will get the benefit by checking the progress status which will lead them to be more injury free and boost performance